EVALUATION OF THE IMPLEMENTATION OF THE MERDEKA CURRICULUM USING THE CIPP MODEL IN ELEMENTARY SCHOOLS - Nanci Elyani Panna; Patrisius Rahabav; Lambertus Johanes Lokollo (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study evaluates the implementation of the Merdeka Curriculum in four elementary schools in Baguala District, Ambon City, namely SD Negeri 1 Lateri, SD Negeri 2 Lateri, SD Negeri 2 Passo, and SD Negeri 77 Passo. The study used a qualitative evaluative approach with the CIPP model, consisting of context, input, process, and product evaluation. Data were collected through interviews, observations, and documentation involving principals and teachers as key informants. The results show that, in the context aspect, schools have understood the main principles of the Merdeka Curriculum as flexible, student-centered, and character-oriented learning. In the input aspect, schools have provided training, learning devices, and principal support, although teacher readiness and learning facilities remain uneven. In the process aspect, learning has begun to apply student-centered strategies, project activities, and diagnostic and formative assessment, but differentiated learning has not been implemented consistently. In the product aspect, the curriculum has contributed to students' activeness, confidence, cooperation, literacy, numeracy, and Pancasila Student Profile values. The study concludes that the implementation is generally adequate but requires continuous improvement in teacher competence, digital learning facilities, assessment practice, and school-parent collaboration.